Game theoretical routing protocol with fairness problem in wireless mesh networks - Wen-jiang JI; Jian-feng MA; You-liang TIAN; Zhuo MA (Tongxin xuebao)
Based on game theory,a routing protocol studied with irness problem was proposed.Each router had the same opportunities of Internet access no matter how far from the gateway.Based on the tree topology,the calculation of route could be distributed to every branches of the tree,which greatly reduced the load of the root and more suitable for wireless mesh networks.The simulation results show that the new protocol is more suitable for wireless mesh networks compare with AODV and HWMP,no matter in network throughput or average end-to-end delays,as far as fairness.